African matrilineages in American Creole cattle: Evidence of two independent continental sources - Liron, Juan Pedro (2006)
In order to clarify the historical origin and phylogeographic affinities of Creole cattle matrilineages throughout the American continent, we analysed published D-loop mtDNA sequences (n = 454) from Creole, Iberian and African cattle breeds. The Western European T3 haplogroup was the most common in American Creole cattle (63.6%), followed by the African T1 (32.4%) and the Near Eastern T2 haplogroups (4%). None of the sequences were found in Bos indicus types. Within the African T1 haplogroup there were two subclades, T1a and T1*, whose geographic distribution in America was clearly disjointed. T1a is a highly divergent clade originally reported for Creole cattle from Brazil and the Lesser Antilles, but whose geographic distribution in Africa remains unknown. In contrast, lineages attributable to T1* are restricted in America to the region colonized by the Spaniards. We propose a new hypothesis for the origins of Creole cattle that summarizes all previously published historical and genetic data. While the African T1* fraction in Creole cattle may have arrived in America through the Iberian breeds, the divergent T1a lineages may have been introduced by Portuguese and other European crowns from some unknown, not-yet-sampled African location. Additional molecular studies will be required for pinpointing the specific African regional source.